Zastosowanie Transformacji Laplace'a i Funkcji Schodkowych w Teorii Belek o Zmiennej Sztywności - Iwiński, T. (Engineering Transactions, 1964)
By applying the theory of step functions and the Laplace transformation the author gives a method for solving the differential equation (1.1) derived on the grounds of the elementary bending theory and concerning the problem of a beam of variable rigidity. Two solution methods are described, The first, operational method, is based on Eqs. (1.4) - (1.6) the operators of Laplace transformation, e and Q-1, being involved. The other method which is analytic (the symbols  and L-1 being no more used) is based on Eqs. (1.4) and (1.13)-(1.19). The latter method coincides with the solution of SH. E. MIKELADZE, [6]. An example shows how the operational form of solution can be used to solve a particular engineering problem.In the second part a method is proposed for solving boundary value problems. This method can be used to solve a boundary value problem without precising the load on the beam. Owing to this considerable generality and economy of labour is obtained in computations of structural mechanics.